ANALISIS KADAR RESIDU PESTISIDA ORGANOFOSFAT DAN ANTIOKSIDAN PADA BAYAM (AMARANTHUS SP) DIPERKEBUNAN KARTAMA KECAMATAN MARPOYAN DAMAI PEKANBARU. - Riski Novera Yenita; Bintal Amin; Christine Jose (Program Pascasarjana Universitas Riau, 2012)
This study has been conducted from May to June 2012 to analyze the levels oforganophosphate pesticide residues and antioxidant in two types of spinach taken fromKartama Plantation District of Marpoyan Damai Pekanbaru. The results showed thatorganophosphate pesticide residues in green spinach were higher than that in red spinach. On the contrery, the levels of antioxidant were found to be higher in green spinach than thered one. In general, there was no significant correlation between pesticide residues andantioxidant in both types of spinach. Nine out of eighteen analyzed samples were exceededthe permissible level of pesticide in commonly consumed vegetables.